PERLINDUNGAN HUKUM ATAS HAK-HAK KELOMPOK AGAMA MINORITAS DI INDONESIA - Bani Syarif Maula (IAIN Syekh Nurjati Cirebon, 2020)
Freedom of religion and belief is part of the basic values contained in human rights. At present, the concept of human rights is generally accepted as a principle for all countries in the world regardless of ideology, politics, economy and social conditions. In Indonesia, efforts to democratize after the fall of the New Order regime are not in line with the guarantee of human rights for minority groups, especially in relation to freedom of religion and belief. In 2019, the condition of religious freedom in Indonesia generally tends to be negative compared to the previous year. This paper examines how legal protection of the rights of religious minorities is carried out in Indonesia. The conclusion of this study is that there are many provisions in the 1945 Constitution and in its legal system that support religious freedom, however, some discretionary powers granted to the government have made serious implications for the enforcement of these constitutional rights.